Mobility status, nutritional intervention and meal eaten are associated with discharge home: the nutritionDay study in China - Zhou, Bei; Zhang, Yupeng; Gao, Xuejin; Liu, Sitong; Shen, Ruting; Huang, Yingchun; Zhao, Yang; Zhang, Li; Wang, Xinying (Frontiers in Nutrition, 2025)
ObjectivesReduced mobility during hospitalization can trigger complications and worsen the prognosis of critically ill patients. However, evidence regarding the combined effects of mobility status and nutritional characteristics on inpatients is scarce. This study aimed to evaluate how inpatients’ mobility status, nutritional intervention, and meal eaten affect discharge home and to further explore the relationship between reduced mobility and nutritional characteristics.MethodsThis was a prospective cross-sectional nutritionDay study conducted at 20 centers in China from 2010 to 2020. The sample was divided into mobile and reduced mobility groups. Cox regression models were used to identify the potential effects of nutritional intervention, meal eaten, and mobility status on discharge home. Logistic regression models were used to identify the association between reduced mobility and nutritional characteristics. Subgroup analyses were conducted to evaluate the association between mobility status and discharge home according to different nutritional interventions, meal eaten, survey years, and regions. Sensitivity analyses were performed to assess the robustness of the findings.ResultsA total of 5,511 adult patients were included. Mobile patients who could walk unaided had a 1.2 to 1.3 times higher chance of discharge home and a significantly shorter duration of hospital stay after nutritionDay than those with reduced mobility, especially in patients receiving artificial nutrition (median: 8 days vs. 11 days, p < 0.001) and those with incomplete meal intake (median: 6 days vs. 8 days, p < 0.001). In multivariable models accounting for other parameters, patients receiving dietary nutrition had a 0.45 (95% CI [0.36–0.55], p < 0.001) lower probability of reduced mobility compared with patients receiving artificial nutrition, and patients who ate their meals completely had a 0.34 (95% CI [0.28–0.41], p < 0.001) decreased chance of reduced mobility compared with those with incomplete meal intake.ConclusionWalking unaided was associated with a higher chance of discharge home, particularly in patients receiving artificial nutrition and those with incomplete meal intake. The likelihood of reduced mobility can be estimated by nutritional intervention and meal eaten on the same day. Further studies are required to validate causal inference and improve inpatient mobilization by addressing relevant influencing factors.